Analisis 5 (Lima) Tahapan Proses Keputusan Pembelian Terhadap Pengambilan Keputusan Mahasiswa Universitas 45 Surabaya Dalam Memilih Perguruan Tinggi - Okky Novianto; Harsono Teguh Santoso; Rina Dewi; Bambang Karnain; Sugiharto Sugiharto; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to find out and understand how University 45 Surabaya students make decisions in choosing a university which is analyzed through 5 (five) stages of the purchasing decision process, namely Problem Recognition, Information Search, Evaluation of Alternatives, Purchase Decision, and Postpurchase Behavior. The population in this study were all active students in the 2014-2016 academic year at University 45 Surabaya. Determining the sample for this study used probability sampling with proportional sample strata. The type of research is qualitative research. The analytical tool used is a descriptive statistical method through calculating the size of central tendency by looking for the average value (mean) at the Problem Recognition, Information Search, Evaluation of Alternatives, Purchase Decision stages, and the IPA (Importance-Performance Analysis) method for the Postpurchase Behavior stage which is used to rank various elements of service quality through the aspects of Expectation (expectations) and Performance (performance). Research results in stage I Problem Recognition (Problem Recognition), there is a total score of 371 with an average value of 74.20 and the lowest namely 322 with an average value of 64.40. where the total average is 712.40. At the Information Search stage, the highest total score was obtained, namely 378 with an average value of 75.60 and the lowest total score was 244 with an average value of 48.80, where the total average was 679.00. At the Evaluation of Alternatives stage, the highest total score was obtained, namely 378 with an average value of 75.60 and the lowest total score was 241 with an average value of 48.20, where the total average was 661.00. At the Purchase Decision stage, the highest total score was obtained, namely 369 with an average value of 73.80 and the lowest total score was 262 with an average value of 52.40, where the total average was 812.60.